Chromosomal Abnormalities (IntechOpen, 2023)
This edited book, Chromosomal Abnormalities - A Hallmark Manifestation of Genomic Instability, contains a series of chapters highlighting several aspects related to the generation of chromosomal abnormalities in genetic material. We are extremely grateful to the authors who had contributed with valuable information about the role of genomic instability in pathological disorders as well as in the evolution process.